PENERAPAN PERMAINAN TRADISIONAL UNTUK MENGATASI KEJENUHAN BELAJAR PJOK DI KELAS V SDN PARANG TAMBUNG 1 - Randi Apandi; Andi Atssam Mappanyukki (Jurnal Education, 2024)
The aim of this research is to find out whether the application of traditional games can overcome the boredom of learning PJOK for class IV students at Parang Tambung State Elementary School 1 semester II of the 2023/2024 academic year. This type of research is classroom action research (PTK) with the research subjects being 20 class IV students of Parang Tambung 1 State Elementary School. Meanwhile, the object of this research is reducing student learning boredom by implementing traditional games. Data on the results of the learning implementation were collected using a questionnaire method. The data obtained was analyzed using descriptive statistical analysis. Based on the results of data analysis, it can be concluded that the application of traditional games is very effective in overcoming learning burnout for class IV students at Parang Tambung State Elementary School 1 semester II of the 2023/2024 academic year. The average decrease in student learning boredom is in the very high category. Meanwhile, classical completeness is 100%.